UPAYA PENGUATAN KESEHATAN MASYARAKAT: EDUKASI TENTANG PENYAKIT KAKI GAJAH (FILARIASIS LIMFATIK) DI SMA NEGERI 1 AMANUBAN TENGAH, KABUPATEN TIMOR TENGAH SELATAN - Maria Aega Gelolodo; Julianty Almet; Annytha I. R. Detha (Universitas Nusa Cendana, 2021)
Lymphatic Filariasis (LF) or known as elephantiasis is one of the most debilitating neglected tropical diseases. This parasitic disease is a leading cause of permanent disability worldwide and has affected over 120 million people in 83 countries throughout the tropics and sub-tropics areas. In Indonesia, the LF endemic in 28 provinces with the highest prevalent rate comes from the eastern part of Indonesia, especially East Nusa Tenggara that stood at first place in terms of total cases. A total of 23 regencies in East Nusa Tenggara are known as LF endemic areas. Though a prevention program has been implemented, there is still a lack of knowledge and awareness about LF in the community especially the rural community. Moreover, a misconception about the importance of the Mass Drug Administration (MDA) has jeopardized these communities. Poverty and health illiteracy are suspected as the major causes of lack of awareness. The aim of this one health program was to raising community awareness towards LF through school-based health education. This paper discusses the community outreach program conducted in SMAN 1 Amanuban Tengah. Serial presentations about the disease, the social stigma, its prevention, control, and medication programs had been applied in this program. Raising awareness about the disease, the importance of its prevention, control, and medication programs, and breaking the negative assumptions about the disease were several prominent results from the program.